ダイ5ジ ナンキョク チイキ カンソクタイ エットウタイ キショウ ブモン ガイホウ - 清野, 善兵衛; セイノ, ゼンベイ; 三枝, 隆次; サエグサ, タカツグ; 鈴木, 信雄; スズキ, ノブオ; 坂口, 威; サカグチ, タケシ; SEINO, Zenbei; SAEGUSA, Takatsugu; SUZUKI, Nobuo; SAKAGUCHI, Takeshi (国立極地研究所, 1963)
P(論文) Meteorological observations at Syowa Base in 5th expedition were maintained in the year 1960-1962. Among scientific disciplines importance was attached to the meteorological section consisting of 4 members, to take various types of observation. General and characteristic features in meteorological observations are summarized in the following. A. Surface observation: 3-hourly observations were made throughout the wintering period, 4 observations were transmitted to Mother Station (Mawson), twice daily. In addition to the specified observations, radiation, sunshine and ground temperature were also observed by continuous selfrecording instrument respectively. The special features of this year is that, compared with the appearance of the annual minimum temperature normally in September in the Antarctic, the minimum occurred in July and it is shown that the average temperature in September was 5.5℃ higher than the normal value. B. Upper air observation: One time (12Z) daily rawinsonde observations were made throughout the year except a few cases of only radiosonde observation. Twice daily (00 and 12Z) rawinsonde observations were made during World Meteorological Interval of Post-IGY (July 16-July 25). All observations were transmitted to Mother Station every day. Equipments used : D-55A type Automatic Direction Finder (Similar type with GMD-1A) JMA-RSII Rawinsonde, 1680 Mc JMA-SIII Radiosonde, 27 Mc 800g Balloon (Latex) CaH_2 Cans for Hydrogen gas to fill balloons. Monthly average temperatures and heights were shown in respective figures. In September, combined with the surface temperature, the strong warm-air inflow throughout the troposphere below 300mb could be seen. A rapid warming in the stratosphere in spring was also clearly observed. Wind rose at some selected pressure levels were shown in Figs. 7-10. In general, the wind is strong in winter, especially in the stratosphere and NE-ly and SW-ly winds are predominant in the troposphere, SW-ly or W-ly in the stratosphere. The E-ly winds were also observed ...